Clinical-grade production and safe delivery of human ESC derived RPE sheets in primates and rodents. (February 2020) - Ben M'Barek, Karim; Bertin, Stéphane; Brazhnikova, Elena; Jaillard, Céline; Habeler, Walter; Plancheron, Alexandra; Fovet, Claire-Maëlle; Demilly, Joanna; Jarraya, Mohamed; Bejanariu, Ana; Sahel, José-Alain; Peschanski, Marc; et al.
Abstract: Age-related macular degeneration as well as some forms of Retinitis Pigmentosa (RP) are characterized by a retinal degeneration involving the retinal pigment epithelium (RPE). Various strategies were proposed to cure these disorders including the replacement of RPE cells using human pluripotent stem cells (hPSCs), an unlimited source material to generate in vitro RPE cells. The formulation strategy of the cell therapy (either a reconstructed sheet or a cell suspension) is crucial to achieve an efficient and long lasting therapeutic effect. We previously developed a hPSC-RPE sheet disposed on human amniotic membrane that sustained the vision of rodents with retinal degeneration compared to the same cells injected as a suspension. However, the transplantation strategy was difficult to implement in large animals. Herein we developed two medical devices for the preparation, conservation and implantation of the hPSC-RPE sheet in nonhuman primates. The surgery was safe and well tolerated during the 7-week follow up. The graft integrity was preserved in primates. Moreover, the hPSC-RPE sheet did not induce teratoma or grafted cell dispersion to other organs in rodent models. This work clears the way for the first cell therapy for RP patients carrying RPE gene mutations ( LRAT, RPE65 and MERTK ).